Seven Steps to Energy Efficiency for Foundries - Rajesh Ransing (Foundry Management and Technology, 2015)
Steve Robinsons of American Foundrymen Society has once argued that foundries with 4% profit margin need to find new sales revenue of US$1 Million to generate US$40,000 operating profits. The case study presented in this paper highlights how an in-process quality improvement exercise resulted in annual saving of US$144,000 by studying in-process data in a melt room on 25 process inputs. Foundry is an energy intensive industry. Energy costs for foundries are around 15% of the cost of castings. In recent years foundries have become energy aware and many have installed energy meters with on-line energy monitoring systems to report energy consumption (kWh) per tonne, charge or furnace with varying sampling frequency. This paper highlights how 7 Steps of 7Epsilon were implemented and in-process data for a foundry was visualised using penalty matrices to discover energy saving opportunities. With ISO 9001:2015 on the horizon there is an urgent need to change the foundry culture - across the world - towards capturing, storing, reusing in-process data as well as organisational knowledge in order to demonstrate in-process quality improvement. The 7Epsilon approach offers a structured methodology for organizational knowledge management as well as in-process quality improvement.